Detecting Tendency of Self-Injury in Adolescents Using Strengths and Difficulties Questionnaire - Widyastuti, Widyastuti; Syamsul Bachri Thalib; Ismarli Muis (International Journal of Education, Vocational and Social Science, 2024)
This study aims to see whether the SDQ can be used as an early detection of self-injury tendencies in adolescents. The data collection method in this study used the Strengths and Difficulties Questionnaire (SDQ) scale which consisted of 25 items. Meanwhile, to measure self-injury tendencies, the Indonesian version of the Self Harm Inventory was used, which consisted of 22 items. Participants in this study were 299 adolescents aged 15-19 years. The results of this study indicate that the subscales of emotional problems, problems with peers, and hyperactivity on the Strengths and Difficulties Questionnaire can predict self-harm behavior in adolescents. Meanwhile, prosocial behavior and behavioral problems cannot predict self-harm behavior in adolescents. Therefore, further research is needed regarding the factors that influence the results of this study.